Strategi Dinas Perumahan Rakyat dan Kawasan Permukiman Kota Jambi dalam Penanganan Permukiman Kumuh - Nur Anggita Rahmadani; Riri Maria Fatriani; Suci Rahmadani (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
Slums are an urban issue that arises due to rapid population growth and the limited capacity of local governments to provide adequate housing and basic infrastructure. This leads to areas with low environmental quality, limited access, poor drainage, and high socio-economic vulnerability. A similar phenomenon occurs in Jambi City, which requires a sustainable handling strategy. This study aims to analyze the strategies implemented by the Department of Public Housing and Settlement Areas of Jambi City in addressing slums and assess their contribution to environmental quality. A descriptive qualitative approach was used to understand the policies, program implementation mechanisms, and institutional challenges. Data was collected through interviews with government officials, field observations, and analysis of planning documents. The results indicate that the strategy focuses on improving basic infrastructure, such as road construction, drainage rehabilitation, and the provision of settlement facilities. This program enhances environmental quality and accessibility but faces challenges such as budget limitations, suboptimal inter-agency coordination, and the socio-economic conditions of the community. Addressing slums requires a more comprehensive approach, including collaborative governance, increased community participation, and adaptive policies to ensure sustainable improvements.